Dillem Wilis Agro-Tourism Branding Designs to Increase Regional Competitiveness in Tourism - Prasetyo, Abdul Rahman; Sayono, Joko; Rahmawati, Nila (KnE Social Sciences, 2023)
Dillem Wilis plantation tour is a coffee bean processing company owned by the Dutch government with an area of 40 hectares. The location is in Dompyong Village, Bendungan District, Trenggalek Regency. This company has the potential for clove plantations, dairy farming, and nature tourism with natural potential surrounded by rivers and locations in hilly areas with attractive views. The ancient buildings of the Dutch government still stand strong with the revitalization that has been carried out by the local government. Agrotourism development is currently a priority program for local governments with the construction of road access and supporting infrastructure. Dillem Wilis Agrotourism also has superior products, such as packaged pasteurized milk and Dillem coffee. The visual architecture of the building, packaging of superior products, and sign systems as well as media for publication of tourist destinations do not have unity. To get the attention and awareness of tourists, a creative strategy is needed through the design of the Dillem Wilis agro-tourism brand. The steps that need to be taken in brand design are: (1) designing a visual identity for Dillem Wilis agrotourism, (2) designing physical communication media, (3) designing digital communication media, and (4) marketing visual property and stationary. To create the right brand awareness, it is very much determined by a consistent visual identity. The visual identity will describe non-physical attributes such as vision and mission, tourism value, and tourism culture. This study aims to: (1) produce a brand identity for Dillem Wilis Agrotourism, (2) Integrate the resources owned by Dillem Wilis Agrotourism in order to form a tourism ecosystem, and (3) generate brand awareness through the implementation of the visual identity design into the Dillem Wilis Trenggalek Agrotourism promotion media project using Tim Brown’s design thinking method which refers to Simon Anholt’s regional branding model for the city branding hexagon. Keywords: brand identity, visual branding, Dilem Willis